Characterization of Porcine Monocyte-Derived Macrophages Cultured in Serum-Reduced Medium - Štěpánová, Hana; Kavanová, Lenka; Levá, Lenka; Vícenová, Monika; Šťastný, Kamil; Faldyna, Martin (Biology, 2022)
The aim of this study was to establish a cell culture system for the generation of porcine monocyte-derived macrophages (MDMs) under reduced-serum conditions. Cultures based on either the Nu-Serum™ Growth Medium Supplement (NUS) or a conventional fetal bovine serum (FBS) were compared, which included the assessment of FBS from two different providers (FBS1 and FBS2). The data obtained confirmed the significant impact of culture conditions on in vitro-generated MDMs. The MDMs cultured under reduced-serum conditions showed increased levels of IL-1β and CD86 mRNA and a proinflammatory cytokine profile, characterized by the increased mRNA expression of IL-23p19, CXCL10, and CCL5. Phagocytic and respiratory burst activities were not adversely affected. Surprisingly, the difference between the two FBSs was much more pronounced than the effect of the reduced-serum supplement. The FBS1 culture conditions gave rise to macrophages with higher surface levels of CD14, CD16, and CD163, a lower CD80 mRNA expression, and an increased induction of IL-10 gene expression. In contrast, none of these trends were observed in macrophage cultures supplemented with FBS2. Instead, the FBS2 culture showed increased levels of IL-1b and CD86 mRNA. In conclusion, reduced-serum culture is a useful tool for in vitro porcine MDM generation, in line with the current research trend of reducing FBS use in biological research.
Keywords: monocyte-derived macrophages; serum reduction; porcine; in vitro; pig